Children’s Empathy and Family Income: The Mediating Role of Family Communication Pattern - Amanda, Gianti; Agoes Salim, Rose Mini (Bina Nusantara University, 2019)
The research examined whether the communication patterns in the family by conversation and conformity orientations served as mediators of the relation between children’s empathy and family income. The research was conducted to parents of children age six to eight years old as the participants (N = 233) in Jakarta, Indonesia. The parents’ completed parent’s questionnaire for children’s empathy, family income, and family communication pattern. The relation analyzed using PROCESS Hayes. The results that the family communication pattern partially mediated the children’s empathy and family income. This research result shows a couple of findings. First, the children who come from a low-income family with family conformity orientation have lower empathy. The second finding is that the children with the family who have family conversation orientation have higher empathy. This second finding works for both low and high incomes family. Besides, only conformity orientation is found to mediate the effect of family income on child’s empathy. This research finds there are connections between family environment and children’s behavior. Developing the children’s empathy going to be positive for their social-emotional outcomes in the future is paramount because the children learn to express and regulate their emotion in a positive way when they have higher empathy.